Essays on the Book of Enoch and other early Jewish texts and traditions - Knibb, Michael A. 1938- (Studia in Veteris Testamenti Pseudepigrapha, 2009)
This volume brings together twenty-one essays by Michael Knibb on the Book of Enoch and on other Early Jewish texts and traditions, which were originally published in a wide range of journals, Festschriften, conference proceedings and thematic collections. A number of the essays are concerned with the issues raised by the complex textual history and literary genesis of 1 Enoch, but the majority are concerned with the interpretation of specific texts or with themes such as messianism. The essays illustrate some of the dominant concerns of Michael Knibb's work, particularly the importance of the idea of exile; the way in which older texts regarded as authoritative were reinterpreted in later writings; and the connections between the apocalyptic writings and the sapiential literature.